Cover Picture: Why Are Dithienylethene‐Linked Biscobaltocenes so Hard to Photoswitch? (ChemPhysChem 6/2017). Issue 6 (13th March 2017) - Escribano, Alejandra; Steenbock, Torben; Stork, Conrad; Herrmann, Carmen; Heck, Jürgen
Abstract : The Front Cover picture shows an underground railway map symbolizing the great variety of excited‐state pathways upon photoexcitation, of which only one leads to the desired target. More information can be found in the Full Paper by J. Heck and co‐workers onpage 596 in Issue 6, 2017 (DOI:10.1002/cphc.201601146 ).